Anti‐Vascular Endothelial Growth Factor and the Evolving Management Paradigm for Retinopathy of Prematurity. Issue 3 (May 2018) - Darwish, Dana; Chee, Ru‐Ik; Patel, Samir N.; Jonas, Karyn; Ostmo, Susan; Campbell, Peter J.; Chiang, Michael F.; Chan, Paul R.V.
Abstract : Abstract: : Diagnosis and management of pediatric retinal conditions such as retinopathy of prematurity (ROP) have been evolving significantly with the availability of new technology and treatments. New imaging systems, telemedicine, tele‐education, and anti‐vascular endothelial growth factor (VEGF) intravitreal pharmacotherapy are all changing the way we diagnose and deliver care to children with pediatric retinal disease. Fluorescein angiography and optical coherence tomography have the potential to improve our diagnosis and management of disease, and with improvements in retinal imaging, telemedicine is becoming more feasible. Telemedicine, tele‐education, and computer‐based image analysis may overcome many of the challenges we face in providing adequate care and access for children with pediatric retinal disease. Treatment options have also expanded with the use of anti‐VEGF therapy. Although the use of intravitreal anti‐VEGF for ROP has been documented in the literature for more than a decade, many questions still remain about its safety in the pediatric patient population. Several ongoing prospective studies are exploring the utility of anti‐VEGF agents for ROP, with attention to the optimal dose of drug, systemic safety, and our understanding of recurrence of disease. This review aims to provide an update on current diagnostic and therapeutic modalities, focusing predominantly on the role of anti‐VEGF therapy, for the management of ROP and other pediatric retinal vascular diseases.